Employability traits for engineers: A competencies-based approach. Issue 5 (October 2019) - Pais-Montes, Carlos; Freire-Seoane, Maria Jesus; López-Bermúdez, Beatriz
Examination of the transition of successful students from university into the labour market reveals a significant gap between the competencies acquired during higher education and those needed in the workplace. In this article, the authors discuss a research study undertaken to analyse the employability traits of engineers who had recently graduated. In order to do this, an estimation was made of both acquired and applied competencies in each area of engineering examined (computer engineers, naval engineers and industrial engineers). This analysis enabled the calculation of a choice model to clarify which competencies act as a stimulus for employment and which discourage recruitment. The results provide clear policy directions both for management teams in each of the three areas of engineering and for universities.